Perancangan Sistem Informasi Kerjasama Pada Fakultas Teknik Universitas Sebelas Maret Surakarta. - Muryono, Langgeng; Hastomo, Mursid Dwi; Wibowo, Kresno Ario Tri (Politeknik Harapan Bangsa Surakarta, 2023)
The Faculty of Engineering, Universitas Sebelas Maret Surakarta (UNS) cooperates with various external parties. The recording and archiving of collaboration data is already using a computer by utilizing the Microsoft Excel application. This collaboration data recording system needs to be improved by switching to a website-based information system. It aims to facilitate the search for cooperation data, recording cooperation data and making cooperation reports. By utilizing the website, collaboration data can be accessed at any time without having to search for the physical files. Based on the problems above, the authors formulate the problem to be solved in this study is